2019
DOI: 10.1103/physrevlett.122.208001
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Stretching of Entangled Ring Macromolecules

Abstract: Huang, Q.; Ahn, J.; Parisi, D.; Chang, T.; Hassager, O.; Panyukov, S.; Rubinstein, M.; Vlassopoulos, D.In the melt state at equilibrium, entangled nonconcatenated ring macromolecules adapt more compact conformations compared to their linear analogs and do not form an entanglement network. We show here that, when subjected to uniaxial stretching, they exhibit a unique response, which sets them apart from any other polymer. Remarkably, whereas both linear and ring polymers strain-harden, the viscosity of the rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 41 publications
5
93
0
Order By: Relevance
“…This view of silk registration is highly idealised, in particular because associating polymers exhibit a broad stretch distribution in steady-state flow. Indeed, akin to ring polymers [ 55 , 56 ], rare events of large chain stretches emerge below the stretch transition. We speculate that the width of the distribution determines how likely it is for equally stretched polymers to associate with each other, such that a correlated ‘registered’ network may form.…”
Section: Discussionmentioning
confidence: 99%
“…This view of silk registration is highly idealised, in particular because associating polymers exhibit a broad stretch distribution in steady-state flow. Indeed, akin to ring polymers [ 55 , 56 ], rare events of large chain stretches emerge below the stretch transition. We speculate that the width of the distribution determines how likely it is for equally stretched polymers to associate with each other, such that a correlated ‘registered’ network may form.…”
Section: Discussionmentioning
confidence: 99%
“…Although the combination of various polymer architectures (linear, star, dendritic) and amphiphilicity has attracted a great deal of attention, amphiphilic ring polymers have hardly been studied up to date. This is an important missing piece of the picture, as ring polymers are known to be significantly different from linear ones in a number of ways, including their overall statistical-mechanical properties [36,42], their rheology [32], and their ability to form specific types of threading that result into glassy states in the melt [30,37,38,54]. Cyclic block copolymers that feature chemically distinct sequences are thus forming excellent experimental systems to study the self-assembly of block copolymer rings in finite concentration [31,55,65].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al observed an apparent correspondence between the high-rate extensional viscosity η ex of ring and linear melts of Polystyrene (PS) with the same M w = 185 kg/mol, leading them to propose that rings transition to behaving like linear chains as they elongate [7]. However, prior simulation studies of unentangled ring and linear melts under planar extension did not observe a clear correspondence at large W i [12].…”
mentioning
confidence: 99%
“…Prior studies on this bead-spring model have measured τ e ≈ 1.98 × 10 3 [14]. Figure 2 plots the normalized extensional viscosity η ex /η N ex versus reduced time t/τ ring for a bead-spring melt of rings alongside the experimental curves from Huang et al [7]. Both simulation and experiment use 52.…”
mentioning
confidence: 99%